Bawaslu's Strategy in Preventing Ballot Counting Violations in the 2024 DPRD Election Stages in Lahat Regency - Dhea Miftahul Jannah; Doris Febriyanti; Amaliatulwalidain (Universitas Muhammadiyah Palu, 2026)
This study aims to analyze the strategy of the General Election Supervisory Agency of BAWASLU Lahat Regency in preventing violations at the ballot counting stage in the 2024 DPRD Election. The focus of the research is directed to identify forms of violations that have the potential to occur and evaluate the effectiveness of prevention strategies implemented by Bawaslu, in order to ensure the integrity and transparency of election results. The method used in this study is a qualitative method with a phenomenological approach. The data collection technique was carried out through observation, in-depth interviews with the Lahat Regency Bawaslu, and documentation. This study also uses the Miles and Huberman model data analysis techniques consisting of data reduction, data presentation, and conclusion drawn. The results of the study show that the Lahat Regency Bawaslu has implemented various violation prevention strategies, such as surveillance patrols, community involvement through socialization and public participation, as well as the use of information technology such as the Siwaslu and Sirekap applications. However, several obstacles are still found, including limited human resources, uneven public awareness, and technical obstacles in the operation of digital systems. The evaluation of the strategy shows the need for improvement in inter-agency coordination and strengthening the capacity of field supervisory officers. In conclusion, the prevention strategy carried out by Bawaslu is quite effective but still needs strengthening, especially in terms of officer training, optimization of supervision technology, and increasing public awareness. This study suggests that Bawaslu improve the quality of socialization and political education to the public, strengthen coordination with law enforcement officials, and continue to develop a technology-based supervision system so that the implementation of elections can take place in an honest, fair, and transparent manner.